2016
DOI: 10.3847/0004-637x/822/1/21
|View full text |Cite
|
Sign up to set email alerts
|

The Rotation of the Hot Gas Around the Milky Way

Abstract: The hot gaseous halos of galaxies likely contain a large amount of mass and are an integral part of galaxy formation and evolution. The Milky Way has a2 10 6 K halo that is detected in emission and by absorption in the O VII resonance line against bright background active galactic nuclei (AGNs), and for which the best current model is an extended spherical distribution. Using XMM-Newton Reflection Grating Spectrometer data, we measure the Doppler shifts of the O VII absorption-line centroids toward an ensemble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 67 publications
(148 reference statements)
14
78
1
Order By: Relevance
“…These large uncertainties aside, Figure 5 indicates that the dominant ionization state of oxygen along sightlines through the Galactic halo is O vii. While the location of this O vii is debated (Wang et al 2005;Hodges-Kluck et al 2016;Faerman et al 2017), the gas must contribute a large column density of electrons for any FRB event. There is no apparent correlation (Pearson correlation coefficient of 0.04 and p-value of 0.82) and we conclude that the O vii gas lies beyond the Galactic ISM.…”
Section: The Hot Galactic Halomentioning
confidence: 99%
“…These large uncertainties aside, Figure 5 indicates that the dominant ionization state of oxygen along sightlines through the Galactic halo is O vii. While the location of this O vii is debated (Wang et al 2005;Hodges-Kluck et al 2016;Faerman et al 2017), the gas must contribute a large column density of electrons for any FRB event. There is no apparent correlation (Pearson correlation coefficient of 0.04 and p-value of 0.82) and we conclude that the O vii gas lies beyond the Galactic ISM.…”
Section: The Hot Galactic Halomentioning
confidence: 99%
“…It is noted that the ω value for the hot halo gas is close to but slightly smaller than the ω value for the spiral pattern, although there is no obvious direct explanation. Hodges-Kluck et al [88] suggested that outflows from the disk into the halo may follow galactic rotation but eventually lag behind the gas in the disk. Expectations for the bulge bar vary.…”
Section: Angular Rotation and Orbitsmentioning
confidence: 99%
“…For the hot gaseous halo around the Milky Way (within 50 kpc) at a temperature near 2 × 10 6 K, one can use at a radius of 8.0 kpc the observed rotation velocity 183 ± 41 km/s around the Galactic Center [88].…”
Section: Angular Rotation and Orbitsmentioning
confidence: 99%
“…Both the Milky Way (MW) and M31 have a hot 10 6−7 K circumgalactic medium (CGM) of enormous mass and extent, possibly dwarfing the baryon content of the disks themselves (Anderson & Bregman, 2011;Hodges-Kluck et al, 2016;Lehner et al, 2015). This gas may cool and condense, feeding the disk.…”
mentioning
confidence: 99%